4‐Biphenylylcalcium Iodide and 9‐Phenanthrylcalcium Bromide: Grignard‐Type Reagents of Polycyclic Aromatic Hydrocarbons. Issue 32 (20th June 2013) - Köhler, Mathias; Langer, Jens; Fischer, Reinald; Görls, Helmar; Westerhausen, Matthias
<x xml:space="preserve">Abstract</x> Reduced to the max: Halogenated polycyclic hydrocarbons can be reduced with calcium via two different pathways yielding radical anions due to electron transfer into the π*‐orbital or Grignard‐type reagents due to insertion of Ca into the carbonhalogen bond (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>